2019
DOI: 10.26502/jrci.2644-2809007
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography Findings of Traumatic Brain Injury in Patients with Head Trauma Presenting at the Tamale Teaching Hospital, Ghana

Abstract: The purpose of this study is to report computed tomography (CT) findings of traumatic brain injury (TBI) in patients who underwent head CT at the Tamale Teaching Hospital (TTH) due to head trauma. Material and methods:A retrospective review of 53 head trauma CT reports covering a two year period in the TTH. Variables extracted to form basis of data included patient gender and age, aetiology of injury, and findings of radiologists. Data was processed and analysed with the Statistical Package for the Social S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
(27 reference statements)
1
0
0
Order By: Relevance
“…Extra-cranial lesions were detected in more than half of patients compared to intracranial lesions. [8,17,19,[25][26][27] e findings of the present study corroborate with Rai et al [8] who reported a similar pattern of extra-cranial lesions and intracranial lesions. ere was no statistical difference in the proportion of patients diagnosed with sinusitis and brain neoplasm (tumor, metastasis, and cyst) when CT was contrast enhanced.…”
Section: Discussionsupporting
confidence: 92%
“…Extra-cranial lesions were detected in more than half of patients compared to intracranial lesions. [8,17,19,[25][26][27] e findings of the present study corroborate with Rai et al [8] who reported a similar pattern of extra-cranial lesions and intracranial lesions. ere was no statistical difference in the proportion of patients diagnosed with sinusitis and brain neoplasm (tumor, metastasis, and cyst) when CT was contrast enhanced.…”
Section: Discussionsupporting
confidence: 92%